Sie sind auf Seite 1von 2

Table of Integrals*

Basic Forms x dx = a+x x(a + x) a ln x+ x+a (25) ln axdx = x ln ax x 2 (2b2 + abx + 3a2 x2 ) ax + b (26) 15a2 ln ax 1 dx = (ln ax)2 x 2 ln(ax + b)dx = 1 x(ax + b)dx = 3/2 (2ax + b) ax(ax + b) 4a (27) b2 ln a x + a(ax + b) x+ b a ln(ax + b) x, a = 0 (42) (43) Integrals with Logarithms

1 x dx = xn+1 n+1
n

(1) (2) (3) (4)

1 dx = ln |x| x udv = uv vdu

x ax + bdx =

(44)

1 1 dx = ln |ax + b| ax + b a Integrals of Rational Functions

ln(x2 + a2 ) dx = x ln(x2 + a2 ) + 2a tan1

x 2x (45) a

1 1 dx = (x + a)2 x+a (x + a)n dx = (x + a)n+1 + c, n = 1 n+1 (x + a) ((n + 1)x a) (n + 1)(n + 2)


n+1

(5) (6)

x3 (ax + b)dx =

b b2 x 2 + x3 (ax + b) 12a 8a x 3 b3 + 5/2 ln a x + a(ax + b) (28) 8a

ln(x2 a2 ) dx = x ln(x2 a2 ) + a ln

x+a 2x (46) xa

ln ax2 + bx + c dx = 2x +

1 a

2ax + b 4ac b2 tan1 4ac b2 (47)

x(x + a)n dx =

(7)

1 x2 a2 dx = x 2

1 x2 a2 a2 ln x + 2

x2 a2 (29)

b + x ln ax2 + bx + c 2a bx 1 x2 2a 4 1 b2 + x2 2 2 a

1 dx = tan1 x 1 + x2 1 1 x dx = tan1 a2 + x2 a a x 1 dx = ln |a2 + x2 | a2 + x2 2 a2 x x dx = x a tan1 + x2 a


2

(8) (9) (10) x (11) (12) 1 x dx = sin1 a a2 x2 (13) x dx = x2 a2 x dx = a2 x2 x2 1 dx = x 2 a2 x2 a2 (33) a2 x2 dx = 1 x 2 a2 x2 + 1 2 x a tan1 2 a2 x2 (30)
3/2

x ln(ax + b)dx =

ln(ax + b)

(48)

1 2 x2 a2 dx = x a2 3

(31)

x3 1 1 dx = x2 a2 ln |a2 + x2 | 2 + x2 a 2 2 1 2 2ax + b dx = tan1 ax2 + bx + c 4ac b2 4ac b2 1 1 a+x dx = ln , a=b (x + a)(x + b) ba b+x x a dx = + ln |a + x| (x + a)2 a+x x 1 dx = ln |ax2 + bx + c| + bx + c 2a 2ax + b b tan1 a 4ac b2 4ac b2 Integrals with Roots 2 x adx = (x a)3/2 3 1 dx = 2 x a xa 1 dx = 2 a x ax

1 dx = ln x + x2 a2

1 x ln a2 b2 x2 dx = x2 + 2 1 a2 x2 2 2 b

ln a2 b2 x2

(49)

x2 a2

(32) Integrals with Exponentials 1 ax e a

eax dx = (34)

(50)

xeax dx =

(14)

a2 x2

(35)

1 ax i xe + 3/2 erf i ax , a 2a x 2 2 where erf(x) = et dt 0 xex dx = (x 1)ex

(51)

(15)

x2

x2 a2

1 2 a ln x + 2

x2 a2 (36)

(52) eax (53) (54) (55) (56) (57)

ax2

xeax dx =

x 1 2 a a

(16)

ax2 + bx + cdx = +

b + 2ax 4a

ax2 + bx + c a(ax2 + bx+ c) (37)

x2 ex dx = x2 2x + 2 ex x2 eax dx = x2 2x 2 2 + 3 a a a eax

4ac b2 ln 2ax + b + 2 8a3/2

(17) x (18) (19) 1 ax2 + bx + c = 2 a 48a5/2


2 2

x3 ex dx = x3 3x2 + 6x 6 ex ax2 + bx + c xn eax dx = ax2 + bx + x (38) xn eax dx = xn eax n a a xn1 eax dx

3b + 2abx + 8a(c + ax ) +3(b3 4abc) ln b + 2ax + 2 a

(1)n [1 + n, ax], an+1

2 2 x x adx = a(x a)3/2 + (x a)5/2 3 5 ax + bdx = 2b 2x + 3a 3 ax + b

(58)

(20)

1 1 dx = ln 2ax + b + 2 a ax2 + bx + c

where (a, x) = a(ax2 + bx + c) (39)


x

ta1 et dt

(21) (22) (23) x 1 dx = ax2 + bx + c a ax2 + bx + c b 3/2 ln 2ax + b + 2 a(ax2 + bx + c) 2a dx x = + x2 )3/2 a2 a2 + x2

(ax + b)3/2 dx =

2 (ax + b)5/2 5a 2a) x a

2 i eax dx = erf ix a 2 a 2 eax dx = erf x a 2 a xeax dx =


2

(59) (60) (61)

2 x dx = (x 3 xa

(40)

1 ax2 e 2a

or suitability of this material for any purpose. This work is licensed under the Creative Commons Attribution-Noncommercial-No Derivative Works 3.0 United States License. To view a copy of this license, visit http://creativecommons.org/licenses/by-nc-nd/3.0/us/ or send a letter to Creative Commons, 171 Second Street, Suite 300, San Francisco, California, 94105, USA.

2012. From http://integral-table.com, last revised September 8, 2012. This material is provided as is without warranty or representation about the accuracy, correctness

x dx = ax

x(a x) a tan

x(a x) xa

(24)

(a2

(41)

x2 eax dx =

1 4

x ax2 erf(x a) e a3 2a

(62)

Integrals with Trigonometric Functions sec3 x dx = 1 sin axdx = cos ax a sin2 axdx = x sin 2ax 2 4a (63) sec x tan xdx = sec x (64) sec2 x tan xdx = sin axdx = 1 cos ax a
2 F1 n n

1 1 sec x tan x + ln | sec x + tan x| 2 2

(84)

ex cos xdx =

1 x e (sin x + cos x) 2

(106)

(85) (86)

ebx cos axdx =

1 ebx (a sin ax + b cos ax) a2 + b2 1 x e (cos x x cos x + x sin x) 2 1 x e (x cos x sin x + x sin x) 2

(107)

1 sec2 x 2

xex sin xdx = (87) xex cos xdx = (88)

(108)

1 1n 3 , , , cos2 ax 2 2 2 3 cos ax cos 3ax + 4a 12a 1 sin ax a

1 sec x tan xdx = secn x, n = 0 n (65) x = ln | csc x cot x| + C csc xdx = ln tan 2 1 csc axdx = cot ax a
2

(109)

sin3 axdx =

(66) (67) (68)

Integrals of Hyperbolic Functions (89) cosh axdx = 1 1 csc3 xdx = cot x csc x + ln | csc x cot x| 2 2 1 csc x cot xdx = cscn x, n = 0 n
n

cos axdx =

sin 2ax x cos2 axdx = + 2 4a cosp axdx =


2 F1

1 sinh ax a

(110)

(90) eax cosh bxdx = ax e 2 [a cosh bx b sinh bx] a b2 2ax x e + 4a 2 sinh axdx = 1 cosh ax a

1 cos1+p ax a(1 + p) 1+p 1 3+p , , , cos2 ax 2 2 2 3 sin ax sin 3ax + 4a 12a

(91) (92)

a=b (111) a=b (112)

(69)

sec x csc xdx = ln | tan x| Products of Trigonometric Functions and Monomials

cos3 axdx =

(70)

cos ax sin bxdx =

cos[(a b)x] cos[(a + b)x] ,a = b 2(a b) 2(a + b) (71)

x cos xdx = cos x + x sin x x cos axdx = 1 x cos ax + sin ax a2 a

(93) (94) (95)

sin[(2a b)x] sin ax cos bxdx = 4(2a b) sin[(2a + b)x] sin bx + 2b 4(2a + b)
2

x2 cos xdx = 2x cos x + x2 2 sin x (72) 2x cos ax a2 x2 2 x cos axdx = + sin ax 2 a a3


2

eax sinh bxdx = ax e 2 [b cosh bx + a sinh bx] a b2 2ax x e 4a 2 eax tanh bxdx = (a+2b)x e a a 2bx (a + 2b) 2 F1 1 + 2b , 1, 2 + 2b , e a 1 , 1, 1E, e2bx eax 2 F1 a 1 ax 2b ax e 2 tan [e ] a tanh ax dx = 1 ln cosh ax a

a=b (113) a=b

sin2 x cos xdx =

1 sin3 x 3

(96)

(73)

cos[(2a b)x] cos bx cos ax sin bxdx = 4(2a b) 2b cos[(2a + b)x] 4(2a + b)
2

1 xn cosxdx = (i)n+1 [(n + 1, ix) 2 +(1)n (n + 1, ix)] (74) xn cosaxdx =

a = b (114) a=b (115)

(97)

cos2 ax sin axdx =

1 cos3 ax 3a

(75)

1 (ia)1n [(1)n (n + 1, iax) 2 (n + 1, ixa)] (98)

cos ax cosh bxdx =

sin2 ax cos2 bxdx =

sin[2(a b)x] x sin 2ax 4 8a 16(a b) sin[2(a + b)x] sin 2bx + (76) 8b 16(a + b) sin 4ax x 8 32a (77)

1 [a sin ax cosh bx a2 + b2 +b cos ax sinh bx] (116)

x sin xdx = x cos x + sin x x sin axdx = sin ax x cos ax + a a2

(99) (100) cos ax sinh bxdx = 1 [b cos ax cosh bx+ a2 + b2 a sin ax sinh bx] (117)

sin2 ax cos2 axdx =

1 tan axdx = ln cos ax a tan2 axdx = x + 1 tan ax a

x2 sin xdx = 2 x2 cos x + 2x sin x (78) (79) x2 sin axdx = 2a x 2x sin ax cos ax + a3 a2
2 2

(101) sin ax cosh bxdx = (102) 1 [a cos ax cosh bx+ a2 + b2 b sin ax sinh bx] (118)

tann axdx =
2 F1

tann+1 ax a(1 + n) n+3 n+1 , 1, , tan2 ax 2 2 1 1 ln cos ax + sec2 ax a 2a x 2

(80)

1 xn sin xdx = (i)n [(n + 1, ix) (1)n (n + 1, ix)] 2 (103) Products of Trigonometric Functions and Exponentials

sin ax sinh bxdx =

1 [b cosh bx sin ax a2 + b2 a cos ax sinh bx] (119)

tan3 axdx =

(81)

sinh ax cosh axdx = (82) ex sin xdx = 1 x e (sin x cos x) 2 (104) sinh ax cosh bxdx =

1 [2ax + sinh 2ax] 4a

(120)

sec xdx = ln | sec x + tan x| = 2 tanh1 tan sec2 axdx = 1 tan ax a

(83)

ebx sin axdx =

1 ebx (b sin ax a cos ax) a2 + b2

(105)

1 [b cosh bx sinh ax b2 a2 a cosh ax sinh bx] (121)